Applying the Systems Evaluation Protocol in the real world: Six case studies. Issue 169 (26th April 2021) - Urban, Jennifer Brown; Linver, Miriam R.; Chauveron, Lisa M.; Archibald, Thomas; Hargraves, Monica; Buckley, Jane
Abstract: In this paper, we present six case studies that illustrate the application of the Systems Evaluation Protocol (SEP) in different real‐world implementation conditions. The SEP is a step‐by‐step guide for how to implement Relational Systems Evaluation (RSE), accounting for the complex factors inherent in the larger systems within which a given program is embedded. We discuss the specific SEP steps used and products developed in each case study project, including an emphasis on how decisions were made to include particular SEP elements in different contexts. The six cases differ in terms of the scale of the programs involved, the nature of the SEP delivery or facilitation process, and the balance among multiple desired outcomes reflecting differential emphases on evaluation capacity building. As such, the cases reported here demonstrate that RSE, as implemented using the SEP, is a widely applicable approach to evaluation and ECB.